Analysis and design of non-linear seismic isolation systems for building structures—An overview - Zhu, Yun-Peng; Lang, Z. Q.; Fujita, Kohei; Takewaki, Izuru (Frontiers in Built Environment, 2023)
In this paper, the development of nonlinear building isolation systems is overviewed. The study summarizes commonly used linear building isolation systems in two categories, which are building base isolation systems and building inter-storey isolation systems. Typical isolators including Lead-Rubber Bearings (LRB), Friction Pendulum Bearings (FPB), inter-storey viscous damper and Tuned Mass Damper (TMD) are reviewed. The analysis and design of linear building isolation systems are also reported. After that, nonlinear building isolation systems are introduced from two aspects based on their dynamic characteristics. They are (i) nonlinear stiffness isolators including Quasi-Zero Stiffness isolators and Nonlinear Energy Sink (NES), and (ii) nonlinear damping isolators including power-law viscous dampers and magnetorheological (MR) dampers. Practical implementations of these nonlinear isolators are introduced. Finally, the analysis and design of nonlinear building isolation systems are discussed. Traditional equivalent linearization approaches and advanced nonlinear frequency design approaches are introduced. The promising applications of the nonlinear frequency design approaches to building isolation systems are also demonstrated in this review paper.